PARADIGMS OF CLINICAL PSYCHOLOGY AND HEALTH: ISSUES IN THE DEVELOPMENT OF THE MENTAL HEALTH MOVEMENT - Umy Yonaevy (Adisam Publisher, 2026)
The paradigm of clinical and health psychology continues to evolve, with a number of issues requiring attention if the mental health movement is to achieve broader and more effective impact. Addressing these issues with a holistic, evidence-based approach can help strengthen efforts to improve mental well-being in communities. By understanding these issues, we can better support the mental health movement and create a more inclusive and supportive environment for all individuals. As such, clinical psychology plays a critical role in improving community mental health, helping individuals to overcome psychological challenges, and supporting them in achieving greater well-being. The mental health movement has made significant progress, but it still faces a number of issues that affect its effectiveness and acceptance in communities. Addressing these issues requires collaboration across sectors, including governments, international organizations, communities, and individuals, to create an environment that supports better mental health. By understanding these issues, we can better support the mental health movement and create a more inclusive and supportive environment for all individuals.